2015
DOI: 10.5507/bp.2014.014
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical significance of liver function abnormalities in patients with acute heart failure

Abstract: Aims. Liver pathology caused by cardiac dysfunction is relatively well recognized, however, its clinical importance has not been fully evaluated. The aim of this study was to assess the prevalence of liver function tests (LFTs) abnormalities and to identify associated factors mediating hepatic impairment in patients with acute heart failure (AHF). Methods. The AHEAD (Acute Heart Failure Database) registry is a database conducted in 9 university hospitals and 5 regional health care facilities in the Czech Repub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…6 Adult studies further correlate the degree of TR with severity of cholestasis. 7,8 Elevated bilirubin has also been known to indicate ongoing right heart disease in the perioperative phase of left ventricular assist device placement and heart transplantation. 9,10 The increased filling pressures are transmitted to the venous system causing congestive hepatopathy.…”
Section: Commentsmentioning
confidence: 99%
“…6 Adult studies further correlate the degree of TR with severity of cholestasis. 7,8 Elevated bilirubin has also been known to indicate ongoing right heart disease in the perioperative phase of left ventricular assist device placement and heart transplantation. 9,10 The increased filling pressures are transmitted to the venous system causing congestive hepatopathy.…”
Section: Commentsmentioning
confidence: 99%
“…Liver function abnormalities are detected in about 75% of AHF patients and are closely related to the severity of disease and clinical findings ( 35 ). In bilateral and right sided AHF, cholestatic type (total bilirubin, gamma glutamyl transferase, alkaline phosphatase) liver dysfunction is detected in patients with moderate-to-severe tricuspid insufficiency, whereas in left sided AHF and hypotension (SBP <100 mm Hg) transaminase elevation is present.…”
Section: Clinical Evaluationmentioning
confidence: 99%
“…Previous studies have shown cholestatic pattern of LFT abnormality in patients with biventricular failure, congestive cardiac failure or in valvular abnormalities such as tricuspid regurgitation [16]. This can be explained by hepatic congestion due to increased venous pressure resulting in cholestasis and elevated ALP and Bilirubin.…”
Section: Discussionmentioning
confidence: 99%